Internalization of The Economic Morality Of Pancasila in Economic Behavior on Economic Education Master Students in Universitas Negeri Malang - Wahyu Rizki Aris Suseno; Sri Umi Mintarti Widjaja; Sugeng Hadi Utomo (CV. AFDIFAL MAJU BERKAH, 2022)
Human behavior related to social life certainly cannot be separated from the study of morality, because in life, humans need to develop an attitude of attention, appreciation, and concern for others, of course, while still internalizing the values of Pancasila in practice. This study uses a qualitative approach to the type of phenomenology. The location of this research is in the Faculty of Economics and Business, State University of Malang. The subject of this research is an active student of Master of Economics Education.The selection of informants carried out in the study was carried out by various criteria using the purposive sampling technique. Data collection techniques using interviews, observation, and documentation. This research concludes that the master students of Economics Education, State University of Malang internalize the economic morality of Pancasila in their economic behavior. Students' knowledge of economic morality is obtained through three educational channels, namely formal, informal, and non-formal education.